2021
DOI: 10.1177/21501327211047781
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition in Community-Dwelling Older Adults Before and After SARS-CoV-2 Infection: A Longitudinal Prospective Study in a Rural Village Struck by the Pandemic

Abstract: Background: Information on the body composition of inhabitants of remote communities during the SARS-CoV-2 pandemic is limited. Using a longitudinal population-based study design, we assessed the association between SARS-CoV-2 infection and changes in body composition. Methods: Community-dwelling older adults living in a rural Ecuadorian village received body composition determinations before and 1 year after the pandemic as well as serological tests for detection of SARS-CoV-2 antibodies. The independent asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…However, the study population has been closely followed and most participants underwent repeated determinations of vascular risk factors during the study years. We did not identify significant changes in vascular risk factors with the exception of a temporary decline in physical activity and dietary habits during the past two years as a result of the SARS-CoV-2 pandemic ( Del Brutto et al, 2021 ). The study included a homogeneous population of older adults of Amerindian ancestry living in a remote rural village, and, therefore, our results may not be generalizable to other races/ethnic groups or to people living in other settings.…”
Section: Discussionmentioning
confidence: 74%
“…However, the study population has been closely followed and most participants underwent repeated determinations of vascular risk factors during the study years. We did not identify significant changes in vascular risk factors with the exception of a temporary decline in physical activity and dietary habits during the past two years as a result of the SARS-CoV-2 pandemic ( Del Brutto et al, 2021 ). The study included a homogeneous population of older adults of Amerindian ancestry living in a remote rural village, and, therefore, our results may not be generalizable to other races/ethnic groups or to people living in other settings.…”
Section: Discussionmentioning
confidence: 74%
“…It could be assumed that those residents had a more severe complications of the disease, accompanied by a worse nutritional status. Likewise, there are several epidemiological studies in which no changes were reported in body composition or nutritional status in recovered COVID-19 patients, both older and younger ones [ 12 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our records did not identify significant changes in CVH metrics with the exception of a transient decline in physical activity and dietary habits among older adults during the past year as a result of the SARS-CoV-2 pandemic. 33 In addition, the treatment gap (< 15% of the population with vascular risk factors received proper therapy during the study years) precluded assessment of the impact of medications on WMH progression. The present study included a homogeneous population of older adults of Amerindian ancestry and our results may not be generalizable to other races/ethnic groups.…”
Section: Discussionmentioning
confidence: 99%